Socio-economics and perceptions of Q-fever infection in a pastoralist system of Kajiado County - Oboge, H.M. (2016)
Q fever is a zoonotic disease caused by Coxiella burnetii which is ubiquitous in nature and it poses a substantial public health concern. Q fever has a potential to cause detrimental effect on human health and its effect can translate to substantial economic losses in affected households. Livestock is the main source of infection in humans. The overall objective of this study was to evaluate the need for surveillance of Q-fever infection within pastoral systems by the relevant health systems in Kenya. The specific objectives were first to describe the knowledge and perception of pastoralist in Kajiado County on the common infectious diseases affecting them and second to estimate the socio-economic impact of Q fever infection in pastoralist households. The study was conducted in the month of May and June 2015 in Namanga, Mashuru and Ngong sub counties of Kajiado County. Seven focus group discussions were conducted with pastoralists and nine key informant interviews were held at the local health facilities with the health workers in-charge by use of interview guides. Data was collected on diseases that affected household members; their perception on the most prevalent diseases; household members response when one is sick; average medical costs incurred for treatment for each of the common infectious diseases; their knowledge of Q fever. Pairwise ranking and scoring methods were used to determine the most common diseases affecting the community. Additionally, data was collected from secondary sources on prevalence of Q fever in humans, cattle, goats and sheep; household monthly incomes; estimated outcomes of primary Q fever infections in humans. Data which was obtained from focus group discussions were used to rank prevalent diseases based on the scores given by pastoralists. Further statistical analysis was done using Kruskal-Wallis one-way analysis of variance to determine if there was a significant difference in the mean ranks of diseases across the focus group discussions held with pastoralists/farmers and key informant interviews held with health workers. The economic cost of Q fever infection in humans was estimated using a deterministic model which was developed in Microsoft Excel spreadsheet. The estimation of economic cost was based on the reported prevalence of Q fever infection among pastoralist households, average monthly incomes, average treatment costs and the number of days’ people stayed away from work due to illness with Q fever. From the focus group discussions with pastoralists, common cold and malaria were prioritized as the most prevalent disease, while pneumonia, malaria, upper respiratory tract infections and typhoid fever were prioritized by health workers as most common diseases. Both the pastoralists and clinicians had no knowledge of Q fever infection amongst household members. Based on previously estimated prevalence of 26% of Q fever in pastoral systems from secondary sources, the economic impact of Q fever infection in a typical pastoralists household was estimated to be Ksh 4,600 per month. The indirect costs attributed to the number of working days lost were greater than the direct costs such as treatment and transport. Q-fever infection is therefore an important febrile disease in humans and more efforts should be put into increasing its awareness among health workers and pastoralist. Therefore, there is need for surveillance of Q fever infection within pastoral systems by the relevant health delivery systems in Kenya. This can be made possible through combined efforts of pastoralist, veterinarians, health workers, environmental scientists and the government.